Potential Mechanisms for Why Not All Antipsychotics Are Able to Occupy Dopamine D3 Receptors in the Brain in vivo - Kiss, Béla; Krámos, Balázs; Laszlovszky, István (Frontiers in Psychiatry, 2022)
Dysfunctions of the dopaminergic system are believed to play a major role in the core symptoms of schizophrenia such as positive, negative and cognitive symptoms. The first line of treatment of schizophrenia are antipsychotics, a class of medications that targets several neurotransmitter receptors in the brain, including dopaminergic, serotonergic, adrenergic and/or muscarinic receptors, depending on the given agent. Although the currently used antipsychotics display in vitro activity at several receptors, majority of them share the common property of having high/moderate in vitro affinity for dopamine D2 receptors (D2Rs) and D3 receptors (D3Rs). In terms of mode of action, these antipsychotics are either antagonist or partial agonist at the above-mentioned receptors. Although D2Rs and D3Rs possess high degree of homology in their molecular structure, have common signaling pathways and similar in vitro pharmacology, they have different in vivo pharmacology and therefore behavioral roles. The aim of this review is to demonstrate that although currently used antipsychotics display substantial in vitro activity for both D3Rs and D2Rs, only very few are actually able to significantly occupy D3Rs, via highlighting preclinical and clinical evidence. The relative importance of the level of endogenous extracellular dopamine in the brain and the degree of in vitro D3Rs receptor affinity and selectivity as determinant factors for in vivo D3Rs occupancy by antipsychotics, are also discussed.